Effects of wood density on mechanical properties of mangrove wood from the Amazon coast. - Madson Lucas Galvão; Adam Bessa-Silva; Alessandra Silva Batista; Bruno Monteiro Balboni; Iedo Souza Santos; Marcus Emanuel Barroncas Fernandes (PLoS ONE)
Mangrove forests are essential on the Amazon coast, as local communities widely use their wood. However, it is still necessary to understand the mechanical properties of wood typical of mangroves. Our main objective was to understand the influence of density on mechanical properties. Then, we tested the hypothesis that wood density has a stronger influence on the mechanical properties of R. mangle trees. Five trees of each dominant mangrove species were cut, and the mechanical properties of wood from these species were analyzed according to ASTM D143-14. Rhizophora mangle wood presented the highest average values compared to other mangrove species for mechanical properties (ρ12% = 1031.6 kg m-3; fv0 = 21.8 Mpa; fc0 = 79.6 Mpa; fM = 190.0 Mpa; EM0 = 18.8 Gpa), as well as for resistance and rigidity. Wood from mangrove trees on the Amazon coast has the same trend of mechanical properties as trees from Asian mangroves. Avicennia germinans and Laguncularia racemosa have a moderate rating. Rhizophora mangle stands out for presenting the highest values of these properties, with the species of Rhizophoraceae being considered the most resistant wood among mangrove species worldwide.